Screening for elder mistreatment in a Swiss emergency department: a prospective cohort study (Swiss Medical Weekly, 2024)
AIM OF THE STUDY: The mistreatment of older adults is a global and complex problem with varying prevalence. As there are no data on the prevalence of elder mistreatment in European emergency department populations, we aimed to translate and culturally adapt the Emergency Department Senior Abuse Identification (ED Senior AID) tool for German use, assess the positive screen rate for elder mistreatment with the German version, and compare characteristics of patients who screened positive and negative.METHODS: To assess the prevalence of elder mistreatment, we created a German version of the ED Senior AID tool. This tool identifies intentional or negligent actions by a caregiver or trusted person that cause harm or risk to an older adult. Then, the German ED Senior AID tool was applied to all consecutively presenting patients aged ≥65 years at our academic emergency department in the Northwest of Switzerland from 25 April to 30 May 2022. Usability was defined as the percentage of patients with completed assessments using the German ED Senior AID tool.RESULTS: We included 1010 patients aged ≥65 years, of whom 29 (2.9%) screened positive with the ED Senior AID tool. The patients who screened positive were older, more severely cognitively impaired, hospitalised more frequently, and presented with higher frailty scores than those who screened negative. Mortality up to 100 days after presentation was comparable in all patients (p = 0.861), regardless of their screening result. The tool showed good usability, with 73% of assessments completed.CONCLUSION: This is the first prospective investigation on the prevalence of elder mistreatment in a European emergency department setting. Overall, 2.9% of patients screened positive using a validated screening tool translated into German.TRIAL REGISTRATION: This study was registered with the National Institute of Health on ClinicalTrials.gov with the registration number NCT05400707.